Insulation level and clearances for 230 kV air insulated substation - Thanasaksiri,T. (2015)
This paper analyzes the insulation level and air clearances of 230 kV air insulated substation. In order to get the BIL, the crest voltage at any equipment are required. By applying simplified calculation method taken from IEEE Std. 1313.2-1999 and IEEE Std. 1427-2006 compared with digital simulation. The simulations have been implemented using simplified models via EMTP-ATP. The BIL required and BIL selected from simplified calculation may give the insulation level not in the range, so the digital simulation would be the better choice. The effect of elevation from sea level as well as the switching surge have been considered for insulation levels and clearances. © 2014 IEEE.